Experimental Study of Two Rows Hybrid Film Cooling Holes Over Flat Plate Surface Using IR Technology - Ahmed A. Naji; Harbi A. Daud; Nabil J. Yasin; Ahmed A. Jasim (Journal of Techniques)
The study examines the effectiveness of two rows of hybrid film cooling holes over a plate surface using infrared technology and a thermal wind tunnel. The two rows consist of seventeen coolant injection holes, with nine in the first row and eight in the second row. Two cases were studied: case 1 using cylindrical holes and case 2 using hybrid holes. Both cases had the same cross-sectional area with a hydraulic diameter of 5.3 mm and a forward coolant injection angle of 30° in the streamwise direction. Different blowing ratios (mass flows ratio between the coolant and mainstream) were tested at 0.5, 1.0, and 1.5. The study focuses on evaluating the impact of hole shape with various blowing ratios on film cooling effectiveness. In addition, thermal images of the test surface were taken via an infrared camera after reaching a steady state. The results indicated that at a blowing ratio of 0.5, there was a significant enhancement in film efficacy, with a decrease in the test surface temperature of the cylinder and hybrid hole cases by 31.8% and 35.0%, respectively, when compared to a blowing ratio of 1.0 and 1.5, which had a temperature increase. Therefore, the film cooling effectiveness decreased to 30.9% and 32.4%, and 29.5% and 31.7% for the cylinder and hybrid hole cases, respectively. Additionally, the better overall film cooling effectiveness in this study was achieved by the configuration of the hybrid holes at a blowing ratio of 0.5, which resulted in a film cooling effectiveness of 35.0%